Innovating organisations and HRM: A conceptual framework - Jan Kees Looise; Maarten van Riemsdijk (Management Revue, 2004)
In November 2003 the Dutch HRM network held its third annual international conference at the University of Twente, Enschede, The Netherlands. Its topic was 'Innovating HRM?', a multi facetted topic that can be elaborated in many ways, as the 10 different tracks of the conference testify. The articles in this special issue are related to two of the tracks, labelled 'Organisational innovation and HRM' and 'Innovating the HR Function'. This first article should be read as an introduction to the five articles from the congress that follow, to position them in the field and to show that again a shift in emphasis seems to announce itself.
Keywords: 650; Organisational Innovation; Human Resource Management; Innovation Management; Network Organisations; Personalmanagement; Organisatorischer Wandel